Evaluation of nursing students' clinical practices: from a patient's perspective - Sakalli, Gulcan Durust; Dag, Gulten Sucu; Payas, Serpil Cagliyan; Tasargol, Omer (Bmc, 2025)
Patient feedback is highlighted as a valuable source for creating learning opportunities. Improving student competencies from the patient's viewpoint is a central focus. The research contributes to establishing standards for clinical performance and skills. This study aims to incorporate patients' perspectives into the evaluation of nursing students. The results may also inform future nursing curriculum development. This is a quantitative, descriptive study. April-December 2023 the study was conducted on patients who underwent surgery in the surgical clinics of a public hospital in Northern Cyprus. The study population consisted of patients who were admitted to the surgical clinics of the public hospital and who agreed to participate in the study. Census sampling was used. The study sample consisted of 192 patients who met the inclusion criteria. Demographic and clinical characteristics of the patients and the evaluation of nursing students by patients' instrument (ENSPA) were used for data collection. A moderate statistically significant difference was determined between the Person-Oriented sub-dimension of ENSPA and the duration of encounter with the student. There was a moderate statistically significant difference between the Caring sub-dimension of ENSPA and the age of the patients. A statistically significant relationship with a moderate correlation was found between the Person-Oriented sub-dimension of ENSPA and the duration of encounter with the student. Similarly, a statistically significant relationship with a moderate correlation was observed between the Caring sub-dimension of ENSPA and the age of the patients. The highest scores were in caregiving, the lowest in honesty and ethical principles, with clinical performance significantly related to hospital stay and interaction duration. Furthermore, students' clinical performance was found to be significantly associated with both the length of patients' hospital stays and the duration of interactions between students and patients.
Keywords: Education; Nursing students; Nursing assessment; Inpatients